1968
DOI: 10.1055/s-0028-1110903
|View full text |Cite
|
Sign up to set email alerts
|

Der Beitrag der Liquorelektrophorese zur klinischen Diagnostik

Abstract: Die klinische Bedeutung der Liquorelektrophorese wurde anhand der Erfahrungen mit über i800 Pherogrammen geprüft. Die Indikationsstellung zur Untersuchung engt sich dabei auf die Erwartung erhöhterund y-Globuline ein. Die Liquorelektrophorese leistet einen wichtigen Beitrag zur klinischen Diagnostik: Bei Pickscher-und Alzheimerscher Krankheit sind die j3 -Globulin-Werte im Liquor erhöht (Mittelwert zz rel. %). Die y-Globulin-Werte im Liquor sind stets erhöht bei unbehandelter Lues cerebrospinalis und subakuter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

1972
1972
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…Erhöhungen oder Erniedrigungen der Beta-Globulin-Fraktion der Liquorelektrophorese feststellten (Bergleiter, Consbruch, Koufen 1967, Consbruch, Koufen 1968, Graune et. al.…”
Section: Diskussionunclassified
“…Erhöhungen oder Erniedrigungen der Beta-Globulin-Fraktion der Liquorelektrophorese feststellten (Bergleiter, Consbruch, Koufen 1967, Consbruch, Koufen 1968, Graune et. al.…”
Section: Diskussionunclassified
“…He was also able to traced the disease to a female ancestor, and called the males "bleeders", already inferring the definition of carriers -women who inherit one affected X chromosome. Before Dr Otto's description, two other possible cases were reported: one on a weekly local newspaper from Salem, USA -a 19-year-old boy, Isaac Zoll, that died from exsanguination like his five brothers -and other from Germany, described in 1793 from G. W. Consbruch of Bielefeld 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, several reports have indicated that the CSF protein fraction changes are variable and largely nonspecific in patients with intracranial mass lesions. 7,8,12,15 The purpose of this study was to analyze the CSF protein fractions in a large group of patients with intracranial mass lesions and to evaluate the diagnostic significance of the findings.…”
Section: Introductionmentioning
confidence: 99%